Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan di RSU Bunda Jembrana - Ni Putu Dian Puspitawati; Nur Wulan Intan Palupi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
In the current era of globalization, various problems must be faced by organizations, from within and outside the organization. Organizations are required to make strategies to be able to deal with existing problems and be able to serve the public or clients properly and optimally. This study aims to examine the effect of work environment, motivation, and the combined effect of work environment and motivation on employee performance at RSU Bunda Jembrana. This research uses quantitative methodology. The research methodology used in is a quantitative approach. The data sources used are primary and secondary. There is primary data obtained from observation methods, interviews, and questionnaires to respondents. Secondary data sources are data from certain records obtained through journals, modules and books in accordance with this research problem. The sample of this study amounted to 20 participants who worked at RSU Bunda Jembrana. This research data analysis through Validity Test, t test, and f test. The findings of this study show that the work environment has a positive effect on work motivation at RSU Bunda Jembrana, motivation has a positive effect on employee performance, and a positive effect of work environment and motivation on overall employee performance.